Strong pyro-electro-chemical coupling of Ba0.7Sr0.3TiO3@Ag pyroelectric nanoparticles for room-temperature pyrocatalysis. (August 2018) - Xu, Xiaoli; Chen, Shijie; Wu, Zheng; Jia, Yanmin; Xiao, Lingbo; Liu, Yongsheng
Abstract: In this work, a strong pyro-electro-chemical coupling effect of the sol-gel-synthesized Ba0.7 Sr0.3 TiO3 (BST) pyroelectric nanoparticles was discovered and its application for room-temperature pyrocatalytic dye decomposition was also developed. Through harvesting 25–50 °C cold-hot alternation energy, BST nanoparticles can obviously decompose Rhodanmine B dye with a decomposition efficiency of 90%. The pyro-electro-chemical coupling is on basis of product of the pyroelectric effect and the electrochemical effect, which can be proved by the observed intermediate reaction products of superoxide radicals (O2 - ) and hydroxyl radicals (OH). The enhanced pyrocatalytic activity of pyroelectric BST@Ag (1.5 wt%) nanoparticles is obtained with a decomposition efficiency of 99% for Rhodanmine B dye, which may be due to the coating silver on BST surface impeding the recombination of pyroelectrically-induced positive and negative electric charges. The strong pyro-electro-chemical performance makes the pyroelectric BST@Ag nanoparticles potential in wastewater decomposition through utilizing cold-hot fluctuation thermal energy. Graphical abstract: fx1 Highlights: A pyro-electric-chemical coupling is discovered in the pyroelectric Ba0.7 Sr0.3 TiO3 nanoparticles. Ba0.7 Sr0.3 TiO3 can pyrocatalytically decompose 90% dye under 25–50 °C cold-hot cycles. The enhanced pyrocatalytic activity is found in Ba0.7 Sr0.3 TiO3 @Ag (1.5 wt%) nanoparticles.